Films, Subtitles and Subversions - Di Giovanni, Elena (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Focusing on subtitling for film festivals, more specifically on an Italian festival on human rights, this paper centres upon the notion of subversion as it can be applied to the practice of subtitling in this very special field. Subversive practices can, in fact, be found at various levels in the overall activity which the international distribution of films through festivals entails. From the very production of films and videos which tend to upturn mainstream cinematic conventions to the translation and dissemination of texts denouncing the violation of rights, the subversive action carried out by film festivals is always visible, strong and steady.Laying emphasis on the often unacknowledged role of the subtitlers involved in these subversive actions, the paper attempts to highlight the unique and often very complex role they are required to play, as well as the linguistic, sociocultural and emotional constraints they have to face.